Konsep Penataan Ruang Berkelanjutan Pada Kawasan Tepian Sungai Musi Kota Palembang (Kasus: Kelurahan 5 Ulu Dan 7 Ulu, Kecamatan Seberang Ulu) - Endy Agustian; Arditia Larasati Utomo (Universitas Islam Sultan Agung Semarang, 2023)
ABSTRACTThe high rate of population growth causes slums in an area, especially in the Musi riverbank, Palembang City. This is marked by the development of community activities, such as economic and industrial sectors in the area. On the other hand, the population growth is relatively rapid and uncontrollable which causes of the settlement areas to become very dense and irregular which can disrupt the function of rivers and river ecosystems. This study aims to formulate a sustainable spatial planning concept on Musi Riverbank in 5 Ulu and 7 Ulu Villages, Seberang Ulu District, Palembang City. The research method used in this study is qualitative with a spatial approach. Data is collected by means of observation, interviews, and document review, then analyzed rby means of qualitative data analysis, spatial analysis, Spradley model analysis, and triangulation analysis. The results of the study show that the analysis of the suitability of riverbank areas in 5 Ulu and 7 Ulu Villages with existing conditions based on economic, socio-cultural and physical aspects. Meanwhile, the concept of sustainable spatial planning in the area is by developing a mixed-used waterfront / riverside arrangement concept with the direction of industrial village development, fulfillment of public space facilities, as well as protected areas and cultivation areas.Keywords: spatial planning, sustainable space, riverbank. ABSTRAKTingginya angka pertumbuhan penduduk menyebabkan terjadinya kekumuhan pada suatu wilayah, khususnya di kawasan tepian sungai Musi Kota Palembang. Hal ini ditandai dengan perkembangan aktivitas masyarakat terutama pada sektor perekonomian dan perindustrian di kawasan tersebut. Di sisi lainnya, pertumbuhan penduduk yang relatif pesat dan tak terkendali yang menyebabkan kawasan permukiman menjadi sangat padat dan tidak beraturan yang dapat mengganggu fungsi sungai dan ekosistem sungai. Penelitian ini bertujuan untuk merumuskan konsep penataan ruang berkelanjutan pada kawasan tepian Sungai Musi di Kelurahan 5 Ulu dan 7 Ulu, Kecamatan Seberang Ulu, Kota Palembang. Metode penelitian yang digunakan dalam penelitian ini ialah kualitatif dengan pendekatan keruangan. Data dikumpulkan dengan cara observasi, wawancara, dan penelitian dokumen, lalu dianalisis dengan cara analisis data kualitatif, analisis spasial, analisis model Spradley, dan analisis triangulasi. Hasil penelitian menunjukkan bahwa analisis kesesuaian kawasan tepian sungai di Kelurahan 5 Ulu dan 7 Ulu dengan kondisi eksisting berdasarkan aspek ekonomi, sosial-budaya, dan fisik. Sementara itu, konsep penataan ruang berkelanjutan pada kawasan dengan mengembangkan konsep penataan mix-used waterfront / riverside dengan arah pengembangan kampung industri, pemenuhan sarana ruang publik, serta kawasan perlindungan dan kawasan budidaya.Kata kunci: penataan ruang, ruang berkelanjutan, kawasan tepian sungai.